The effect of using computer-assisted reading with inquiry-based learning on student reading comprehension - Zakiyuddin Zakiyuddin; Mutmainnah Mustofa; Muhammad Yunus (English Education Journal, 2022)
This study aims to determine whether there is a difference between students who read using computer-assisted reading and those who read using other means in terms of reading. The sample was 23 students studying at two senior high schools in Sumenep, East Java, Indonesia. They were selected from student representatives based on their English language skills. The experiment was divided into six stages which include learning and testing. The researchers used lexical-tutor where there are audio-assisted reading, concordance, and online dictionary. For the learning process, researchers use inquiry-based learning, which focuses on student activity. To determine whether there is an effect on reading comprehension, the researcher used a paired sample t-test and an independent sample test to determine whether there is a difference in student reading comprehension score using an inquiry-based computer aid with those who do not use it. Based on the results of the study, there is no effect and no difference between reading using computer-assisted reading with inquiry-based learning and those who did not use computers. When viewed from individual scores, the results of the study showed little progress. The results of the observation show that not all students like to read while listening to audio.